2017
DOI: 10.1038/sj.bdj.2017.263
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and treatment of invasive cervical resorption in vital teeth. A narrative review and a report of two cases

Abstract: Invasive cervical resorption (ICR) is a significant defect of the root surface where the hard dental tissues are undermined and become translucent due to the resorptive granulomatous tissue. It is mainly detected on radiographs. The radiographic appearance of ICR is asymmetrical radiolucency with irregular margins and an unchanged root canal. The purpose of this study is to present a comprehensive review together with the characteristics and the treatment of ICR through two cases which were followed-up for 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Additionally, a necessary surgical intervention was carried out, which allowed the access and the removal of the resorptive tissue and adequate defect filling, reducing the chances of recurrence [10,11]. During the surgery, Emdogain (Straumann, Fontenay sous Bois, França) was used, which is made up of proteins derived from the enamel matrix, which, in addition to having antimicrobial properties, helps in periodontal regeneration [13,14].…”
Section: Routine Radiographsmentioning
confidence: 99%
“…Additionally, a necessary surgical intervention was carried out, which allowed the access and the removal of the resorptive tissue and adequate defect filling, reducing the chances of recurrence [10,11]. During the surgery, Emdogain (Straumann, Fontenay sous Bois, França) was used, which is made up of proteins derived from the enamel matrix, which, in addition to having antimicrobial properties, helps in periodontal regeneration [13,14].…”
Section: Routine Radiographsmentioning
confidence: 99%
“…The surgical external approaches have been more commonly reported than nonsurgical external approaches perhaps due to the extensive size of the lesions at the time of detection. The surgical techniques reported in studies include removal of the resorptive lesions using TCA and/or mechanical debridement and restoration with hydraulic calcium silicate-based materials or glass ionomer cement [ 51 , 52 , 53 ].…”
Section: Strategies To Manage Icr Lesionsmentioning
confidence: 99%
“…If the resorptive defect is subgingival or subcrestal and accompanies periodontal tissue destruction, it is preferable to use hydraulic calcium silicate-based materials. Several case reports have been published to support the use of hydraulic calcium silicate-based materials for the restoration of ICR defects [ 52 , 53 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Strategies To Manage Icr Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient can be asymptomatic or have difficulties in breastfeeding, speech articulation, and mechanical tasks such as licking the lips, kissing, and oral cavity cleaning. [1–5] It is also reported that ankyloglossia can affect maxillofacial development. [6]…”
Section: Introductionmentioning
confidence: 99%